Effects of the Madrasah Research Program and Flipped Classroom on Students’ Digital Literacy in an Indonesian Madrasah - Qomaruddin, Moch.; Luqman Hakim; Yusuf, Muh. Rizaldi (Universitas Islam Balitar, 2026)
Fostering students’ digital literacy is essential for preparing them with 21st-century skills in the digital era. This study aims to examine the effect of the Research Madrasah Program and the Flipped Classroom learning model on students’ digital literacy skills at MAN 1 Gresik. A quantitative, causal-comparative design was employed involving 60 students selected through purposive sampling. Data were collected using validated and reliable questionnaires and analyzed using descriptive statistics, classical assumption tests, and multiple linear regression. The results show that the Research Madrasah Program significantly enhances digital literacy through habitual research activities and information evaluation, while the Flipped Classroom supports independent, technology-based learning. Together, they explain 60.5% of the variance in students’ digital literacy. These findings imply that integrating research-oriented programs with technology-driven pedagogy creates an active, self-directed, and skill-oriented learning environment, although external factors such as digital access and home support also influence outcomes.